CaO impregnated highly porous honeycomb activated carbon from agriculture waste: symmetrical supercapacitor study - Ali, Gomaa A. M.; Habeeb, Omar Abed; Algarni, H.; K. F., Chong (Scientific Research, 2019)
This study presents the electrochemical studies of activated carbon prepared from palm kernel shell (ACPKS), with CaO impregnation. The CaO is obtained from chicken eggshell waste to produce CaO/ACPKS, which shows highly porous honeycomb structure with homogeneous distribution of CaO nanoparticles (30–50 nm in size). The prepared materials are evaluated as supercapacitor electrodes by testing their electrochemical characteristics. A high specific capacitance value of 222 F g−1 at 0.025 A g−1 is obtained for CaO/ACPKS, which is around three times higher than that for ACPKS (76 F g−1). In addition, electrochemical impedance data show lower impedance for CaO/ACPKS. Lastly, a practical symmetrical supercapacitor is fabricated by CaO/ACPKS and its performance is discussed.